A comparative study of using Kessler Suture Pattern versus Polypropylene meshes implantation to repair Tenotomized Achilles tendon in bucks: Rahi Nahi Al-Asadi and Asaad Alla Mohammad - Al-Asadi, Rahi Nahi (The Iraqi Journal of Veterinary Medicine, 2018)
The aim of the current study was to compare the efficacy of Kessler suture pattern and polypropylene meshes implantation to repair severed Achilles tendons in bucks. For this purpos 16 local adult bucks, weighing 30-35kg were used and equally distributed into two groups, the first group: (control group) and the second group (mesh group). Animals were sedated with xylazine 2% and anesthetized locally with lidocaine hydrochloride 2% infiltrated subcutaneously. Skin incision approximately 5 cm. in length was made over the Achilles tendon. The tendon was isolated by blunt dissection from the underlying tissue, then the left Achilles tendon was transected in its mid portion. In the control group, tenorrhaphy of Achilles tendons were immediately performed by using Kessler suture technique using (polypropylene No. 1). In the second group, a polypropylene mesh was wrapped around the cut ends and fixed to the tendon by simple interrupted stitches of polypropylene thread (No.1). Then skin was sutured by interrupted horizontal mattress using silk No.1. Finally plaster of Paris with window was applied. The skin stitches were removed after 10 days. The clinical signs of all animals showed severe lameness during the first three weeks with no significant differences between the two groups. Lameness reflected significant differences (P<0.05) between groups with the progress of postoperative duration (i.e., starting from 4th week). Rapid absence of lameness was more observed in second group (at 4th week) than in first group (at 6th week). At two months post-operative, a higher percentage (100%) was recorded in first group. While a lower percentage (25%) was showed in the second group. Microscopical examination at two month post-suturing revealed proliferation of fibrous connective tissue around suture materials infiltrated by inflammatory cells, in addition to necrotic tissue attachment to the tendon. In mesh implantation and at the same time there were granulations tissues surrounding the narrow mesh holes with tendon fibers expressed proliferation of tenocytes. At four months, first group revealed few blood vessels, and thickened collagen fibers with mononuclear cells infiltration in cut tendon fibers. In mesh implantation the tendon was retained to its nearly normal structure with few (MNCs) in epitenon. It seemed that both groups gave best outcome in healing of operated tendons with superiority of the second group in comparison with the first group.